DEVELOPMENT AND CORRECTION OF EMOTIONAL INTELLIGENCE OF CHILDREN OF ELEMENTARY SCHOOL AGE IN CONDITIONS OF TEMPORARY CHILDREN’S GROUP - Svatenkova, Tatiana (Social work and education, 2018)
Personality is constantly inclined to experience different emotions every day, but here it is not so easy to understand them. That’s why it’s so important to teach your baby to deal with their emotions correctly and be friends with them. Emotional intelligence or emotional factor (EQ) is "the ability of a person to identify, measure, control, and express emotions." This helps us to communicate with other people more successful, negotiate and produce clear thinking patterns. The article describes the experience of correction and development of emotional intelligence of junior pupils in conditions of being in a temporary children’s environment on the example of the recreation program "Children’s Camp" Zefir ". The special approach to organization of work with children is realized within the framework of the recreation program "Children’s Camp" Zefir" for three years (2015-2018). It’s based on the harmonious combination of socio-pedagogical and individual-psychological approach to the development of the child’s personality. 622 children participated in the study, including 263 junior school age (6-10 years). The optimal training program for the adaptation, increase and correction of the level of emotional intelligence of junior pupils was formed based on the results of the comprehensive diagnosis of each child during the first year of work. In addition to training, individual consultations with the psychologist (based on the results of the methodology) were conducted and the optimal forms of group work were selected based on the general level of group emotional intelligence and test results. Given the results of the study, we have an effective program for working with the emotional intelligence of the child. The positive dynamics, confirmed by the results of three years, helped to develop a training program for working with children during the year, the purpose of which is to plan and harmonize the development of all competences of the modern child.